A conformally flat generalized Ricci recurrent spacetime in F(R)-gravity. (12th May 2021) - De, Avik; Loo, Tee-How; Solanki, Raja; Sahoo, P K
Abstract: In the present paper we study a conformally flat generalized Ricci recurrent perfect fluid spacetime with constant Ricci scalar as a solution of modified F ( R )-gravity theory. We show that a Robertson-Walker spacetime is generalized Ricci Recurrent if and only if it is Ricci symmetric. The perfect fluid type matter is shown to have EoS ω = −1. Some energy conditions are analyzed with couple of popular toy models of F ( R )-gravity, like F ( R ) = R + α R m where α, m are constants and F ( R ) = R + β R ln R where β is constant. In harmony with the recent observational studies of accelerated expansion of the Universe, both cases exhibit that the null, weak, and dominant energy conditions fulfill their requirements whereas the strong energy condition is violated.